2022
DOI: 10.1111/ejn.15732
|View full text |Cite
|
Sign up to set email alerts
|

Termination of seizures in the paediatric age group, best benzodiazepine and route of administration: A network meta‐analysis

Abstract: This network meta‐analysis aims to compare various benzodiazepines and their route of administration using the data published exclusively in randomized controlled trials (RCTs). Two thousand two hundred sixty‐three children presenting with an episode of seizure to ER or to a paramedic where they were administered a benzodiazepine as the first‐line treatment were included. All the outcomes were measured for their mean with 95% CI and rank probability. The primary outcome was the number of successful seizure ces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
0
0
Order By: Relevance
“…Nasal administration of benzodiazepines not only facilitates drug delivery but is also less invasive compared to other routes of administration. Studies have shown that this route of administration takes the least amount of time from administration to seizure cessation, is more effective than intramuscular administration of the drug, and has demonstrated the highest rank probability in total time with the second-highest successful cessation rate in the pediatric population [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nasal administration of benzodiazepines not only facilitates drug delivery but is also less invasive compared to other routes of administration. Studies have shown that this route of administration takes the least amount of time from administration to seizure cessation, is more effective than intramuscular administration of the drug, and has demonstrated the highest rank probability in total time with the second-highest successful cessation rate in the pediatric population [ 95 ].…”
Section: Discussionmentioning
confidence: 99%